2021
DOI: 10.1021/acs.jpcc.1c02227
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Transformation of 2D Layered Perovskites to 3D Perovskites in the Sonochemical Synthesis

Abstract: Two-dimensional (2D) layered Ruddlesden−Popper metal halide perovskites (MHPs) show enhanced stability compared to threedimensional (3D) MHPs. The general formula of 2D layered perovskite is L 2 A n−1 M n X 3n+1 , where L is the large organic spacer and n is the number of metal octahedra. However, the syntheses of such 2D layered perovskites yield a mixture of 3D and 2D layered perovskites with different layers of the metal octahedra. In this work, we have synthesized 2D layered (MA) n+1 Pb n I 3n+1 perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Recently, Wu et al demonstrated the crystal growth of CsPbBr 3 NPl into a nanocrystal via oriented attachments and nanorod formation under different laser excitation sources . With light exposure, different polar solvents like acetonitrile, 2-propanol, methanol, and so forth, as well as heat accelerate similar structural transformation, which was proposed to proceed through the Ostwald ripening type of mechanism. , The effect of light exposure on organic ammonium cation-based RP perovskite films, single crystals, and flakes has different consequences like (i) the degradation of the RP structure into organic amines, PbI 2 , I 2 , and so forth and (ii) the passivation of trap states in RP flakes with a significant role of aerial O 2 . Ha et al explored the fate of UV irradiation on colloidal organic inorganic RP NPls, and they observed photobleaching and formation of higher order layered perovskite structures ( n = 2 to n ≥ 3) that crucially depend on the moisture content . All these observations reveal that light irradiation has a crucial impact on the 2D RP NPls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wu et al demonstrated the crystal growth of CsPbBr 3 NPl into a nanocrystal via oriented attachments and nanorod formation under different laser excitation sources . With light exposure, different polar solvents like acetonitrile, 2-propanol, methanol, and so forth, as well as heat accelerate similar structural transformation, which was proposed to proceed through the Ostwald ripening type of mechanism. , The effect of light exposure on organic ammonium cation-based RP perovskite films, single crystals, and flakes has different consequences like (i) the degradation of the RP structure into organic amines, PbI 2 , I 2 , and so forth and (ii) the passivation of trap states in RP flakes with a significant role of aerial O 2 . Ha et al explored the fate of UV irradiation on colloidal organic inorganic RP NPls, and they observed photobleaching and formation of higher order layered perovskite structures ( n = 2 to n ≥ 3) that crucially depend on the moisture content . All these observations reveal that light irradiation has a crucial impact on the 2D RP NPls.…”
Section: Introductionmentioning
confidence: 99%
“…Like every other perovskite structure, the stability of the 2D RP NPl structure in ambient condition is a paramount concern . The different external perturbations like moisture, heat, solvent, and especially light irradiation affect the 2D structure and introduce different characteristic changes. Shamsi et al studied the transformation of the stacked CsPbBr 3 NPl into green-emitting, larger square-shaped disk and nanobelt structure under UV light irradiation . Roy et al also reported the transformation of quasi-2D MAPbBr 3 NPl into 3D MAPbBr 3 NC under UV light .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the normal NPl structure, in RP NPl the stacking among perovskite layers and their separation by organic ammonium spacer cations make them structurally rigid through interactions like (1) electrostatic interaction, (2) hydrogen-bonding interaction, and (3) van der Waals repulsion . Still, the RP perovskite structure (film, single crystal, or flakes) is affected from different external perturbations like humidity, solvent polarity, temperature, pressure, and especially light irradiation. Under continuous UV-light irradiation, the common consequences are (1) structural transformation, (2) changes in the morphology, and (3) degradation. For a colloidal RP NPl, Ha et al reported the fate of UV-light irradiation on different aliphatic ammonium-based RP NPls, where moisture-assisted structural conversion and photobleaching are two major consequences. Recently, our group also reported the structural conversion of two-dimensional (2D) RP NPls to ambient stable 3D nanorods by UV light …”
mentioning
confidence: 99%
“…Lead-free halide perovskites (LFHPs) are widely employed in photovoltaics and optoelectronic devices due to their nontoxicity, high defect toleration, tunable light frequency, and high photoluminescence (PL) stability. Currently, different metal ions have been adopted to design and synthesize LFHPs with distinct structures. , Divalent metal ions, such as Sn 2+ and Mn 2+ , or trivalent elements, such as In 3+ and Bi 3+ , with similar radii to Pb 2+ , are selected to replace Pb 2+ as the doping or matrix cation to reduce the toxicity and improve the PL properties of LFHPs while maintaining the CsPbX 3 (X = Cl, Br, I) structure or forming unique crystal structures, such as CsSnI 3 , (CH 3 NH 3 ) 2 MnCl 4 , or double perovskite Cs 2 AgIn x Bi 1– x Cl 6 . The incorporation of metal ions into a 3D perovskites crystal to terminate the lattice, forming two-dimensional (2D) or quasi-2D perovskite, has proven to be an effective way of obtaining new materials with unique luminescence properties, such as the broadband emission of self-trapped excitons (STEs), charge transmission, and high photoluminescence quantum yields (PLQYs). Furthermore, 2D perovskites with high formation energy could improve their stability against water and oxygen molecules . Additionally, the rubidium ion (Rb + , 1.52 Å) will be a good choice to replace the cesium ion (Cs + , 1.67 Å) in the perovskite structure due to its smaller ionic radius .…”
Section: Introductionmentioning
confidence: 99%